2015
DOI: 10.1002/marc.201500270
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Triazine‐Based Frameworks as Visible Light Photocatalysts for the Splitting of Water

Abstract: Covalent triazine-based frameworks (CTFs) with a graphene-like layered morphology have been controllably synthesized by the trifluoromethanesulfonic acid-catalyzed nitrile trimerization reactions at room temperature via selecting different monomers. Platinum nanoparticles are well dispersed in CTF-T1, which is ascribed to the synergistic effects of the coordination of triazine moieties and the nanoscale confinement effect of CTFs. CTF-T1 exhibits excellent photocatalytic activity and stability for H2 evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
208
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(213 citation statements)
references
References 38 publications
3
208
0
2
Order By: Relevance
“…In contrastt ob lack CTFs prepared by ZnCl 2 -catalyzed cyclotrimerizationo fc yano-containing aromatic building blocks, [17] DA-CTF prepared by acid-catalyzed reaction is yellow (inset in Figure 2a). The bandgapo fD A-CTF from UV/Vis DRS was 2.35 eV (Figure 2b), which was narrower than that of CTF-T1 (2.94 eV) [18] and reportedc ovalento r- ganic frameworks. Am aximum absorption peak at 400-550 nm was assigned to the p-p*t ransitions of the conjugated aromatic frameworks.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrastt ob lack CTFs prepared by ZnCl 2 -catalyzed cyclotrimerizationo fc yano-containing aromatic building blocks, [17] DA-CTF prepared by acid-catalyzed reaction is yellow (inset in Figure 2a). The bandgapo fD A-CTF from UV/Vis DRS was 2.35 eV (Figure 2b), which was narrower than that of CTF-T1 (2.94 eV) [18] and reportedc ovalento r- ganic frameworks. Am aximum absorption peak at 400-550 nm was assigned to the p-p*t ransitions of the conjugated aromatic frameworks.…”
Section: Resultsmentioning
confidence: 94%
“…[16b] These results demonstrated that DA-CTF holds great promise for the application in CO 2 catalytic conversion. Compared with the light-harvesting efficiency of CTF-T1 prepared from 1,4-dicyanobenzene, [18] the enhanced light absorption of DA-CTF was most likely owing to the introductiono ft he electron-donating triphenylamine group. The UV/ Vis diffuse-reflectance spectrum (UV/Vis DRS) of DA-CTF contained ab road absorption band up to 700 nm;t he addition of 2,2'-bipyridine and Co 2 + had no effecto nt he absorption of DA-CTF (Figure 2a).…”
Section: Resultsmentioning
confidence: 96%
“…[27] Meanwhile, interplanars pacing of 0.27 nm is in accordance with the (1 00) Based on the above,C TFs@MoS 2 -X have ac rystal p-conjugated stacking architecture and hierarchical meso-and micropores in one hybrid system;t his fine structure is facile for fast p-electron hopping,m ass transfer,a nd confinement of the MoS 2 nanoparticles to facilitate large-particle growth. [38] The electrocatalytic performance of as-synthesized CTFs, free MoS 2 ,C TFs@MoS 2 -X, and commercial 20 %P t/C catalysts were evaluated and compared using linear sweep voltammograms (LSV) in 0.5 m H 2 SO 4 solution (N 2 saturated) with at ypical three-electrode system (Figure 4). [28][29][30][31][32][33][34][35] The nitrogen-containing triazine unit in the CTF skeleton can activate the electrons around the carbon,w hich will lead to an outstanding electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…[38] By controlling the structure of the monomers,s uch as introduction of methyl groups,t he optical and electronic properties of the polymers could be manipulated. [38] By controlling the structure of the monomers,s uch as introduction of methyl groups,t he optical and electronic properties of the polymers could be manipulated.…”
Section: Covalent Triazine-based Frameworkmentioning
confidence: 99%